Fountain fringe field switching (FFFS) for wide viewing angle LCDs. (4th February 2022) - Komitov, Lachezar; Barbero, Giovanni; Ibn Elhaj, Mohammed; Morawiak, Przemysław; Piecek, Wiktor
Abstract: To reduce or completely remove the viewing angle dependence of liquid crystal (LC) displays and devices, we have recently introduced a new electrode structure for LC displays. This electrode structure has openings (holes) in the pixel electrode (PixE) for generating fringe electric field with azimuthal degenerated distribution of the field lines around each hole, resembling a fountain. Such a field is promoting azimuthally degenerated switching of the LC molecules and thus generation of images with 360° viewing angle constant contrast when a pair of crossed circular polarisers are used. A theoretical model of the fountain fringe field, generated around a single circular hole and plurality of such holes in the PixE, is presented.